(3OjhGf GdGHjhQOis - (3eMeO Hf CMeO Hf eMeO GdbQTj GdCehj, CHh GdeXaQ, (B507 (3g`s
(3ChdgG (B:s
(3Ndjdi Ef GdMH eG JYQaGfg adG fcQGf Gf GdMfjf ef GdhLO s
(3BNQgG (B:s
(3Rfi Gdbhe MJi JYQai YfO hRfge EPG QaY GdefjQGf cja Cejd s
(3GdfSNI HgG MhGTs
(3Ydi GdfSNI SeGY ef eMehO Hf eMeO Hf CMeO Gdeci GdLfOi Edi CHj SYO CMeO Hf eSYhO GdeaJi GdHNGQis
(3YdjgG TQhM cKjQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs